2006
DOI: 10.1038/sj.bjc.6603013
|View full text |Cite
|
Sign up to set email alerts
|

The influence of allogenic blood transfusion in patients having free-flap primary surgery for oral and oropharyngeal squamous cell carcinoma

Abstract: The influence of perioperative blood transfusion in oral and oropharyngeal squamous cell carcinoma remains uncertain. It is believed that blood transfusion downregulates the immune system and may have an influence on cancer recurrence and survival. In all, 559 consecutive patients undergoing primary surgery for oral and oropharyngeal squamous cell carcinoma between 1992 and 2002 were included in this study. Known prognostic variables along with transfusion details were obtained from head and neck cancer and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 25 publications
6
56
0
Order By: Relevance
“…Haughey et al reported that a cut‐off value of >7 L of crystalloids during surgery resulted in major medical and flap complications. Although several authors demonstrated that preoperatively low hemoglobin levels can have adverse effects on flap success rates,14, 15 there is little support for correction of mild to moderate anemia with blood transfusions due to fear of increased blood viscosity 15, 16…”
Section: Discussionmentioning
confidence: 99%
“…Haughey et al reported that a cut‐off value of >7 L of crystalloids during surgery resulted in major medical and flap complications. Although several authors demonstrated that preoperatively low hemoglobin levels can have adverse effects on flap success rates,14, 15 there is little support for correction of mild to moderate anemia with blood transfusions due to fear of increased blood viscosity 15, 16…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that natural killer cell activity remained higher in the autologous group (p < 0.05) and suggested this as a possible mechanism influencing survival [10]. Furthermore, there is evidence that the increased risk for both infection [5] and disease recurrence [61][62][63] is dose related, with the increased risk of recurrence starting at a threshold of 3-4 units of allogeneic blood transfusion, depending on tumour type.…”
Section: Discussionmentioning
confidence: 99%
“…61 In addition, perioperative blood transfusions have a well-documented association with increased morbidity and mortality, including head and neck cancer recurrence, in free flap reconstruction. 26,27,[62][63][64][65][66][67][68][69] Other studies have suggested a link between blood transfusions and wound infections. 69,70 This association may be caused by an immunomodulatory effect of blood transfusions.…”
Section: Blood Transfusionmentioning
confidence: 99%